Public Narrative of Flood Causes and Solutions in Surabaya - Pravidya Salsabiila; Mohamad Irfan Nafiyanto (Global Writing Academica Researching and Publishing, 2026)
The rainy season has been observed to result in the river reaching its maximum discharge, thereby causing water to be sent into residential areas and roads at approximately 200 points within the Surabaya city area. This phenomenon is further compounded by the inadequacy of the drainage system, which, despite the construction of box culverts in anticipation of the issue, has not yielded substantial results in terms of flood risk management. In confronting these challenges, it is imperative to recognise the pivotal role that community perceptions play in effectively managing and responding to disasters. This study aims to explore the basis of community perceptions regarding mitigation, evacuation, rehabilitation, and the assessment of the city government's flood management strategies in the Surabaya area. The research will implement ethnography virtual research methods by uncovering public narratives generated through comments on “lovesuroboyo” Instagram posts related to flood and culvert box. The discourse in the public sphere has indicated a pervasive sentiment of dissatisfaction with the government for flood risk management. This has led that the culvert box, a primary conduit for flood mitigation, has been adjudged unsatisfactory. In the context of environmental protection and flood management, it is imperative to underscore the significance of two key elements, namely, effective drainage infrastructure and a shared understanding among stakeholders. The necessity for collaboration between government entities and the community as an instrumental means of addressing and mitigating challenges pertaining to flooding.